Subchronic feeding toxicity studies of drought-tolerant transgenic wheat MGX11-10 in Wistar Han RCC rats. (March 2020) - Liu, Yinghua; Zhang, Shujing; Zhou, Qinghong; Li, Shufei; Zhang, Jing; Zhang, Li; Jiang, Shuqing; Zhang, Qian; Zhou, Xiaoli; Wu, Chao; Gu, Qing; Qian, Zhi Yong
Abstract: A subchronic toxicity study were conducted in Wistar Han RCC rats to evaluate the potential health effects of genetically modified (GM), drought-tolerant wheat MGX11-10. Rats were fed a rodent diet formulated with MGX11-10 and were compared with rats fed a diet formulated with its corresponding non-transgenic control Jimai22 and rats fed a basal diet. MGX11-10 and Jimai22 were ground into flour and formulated into diets at concentrations of 16.25, 32.5, or 65%, w/w% and fed to rats (10/sex/group) for 13 weeks. Compared with rats fed Jimai22 and the basal-diet group, no biologically relevant differences were observed in rats fed the GM diet with respect to body weight/gain, food consumption/efficiency, clinical signs, mortality, ophthalmology, clinical pathology (hematology, prothrombin time, urinalysis, clinical chemistry), organ weights, and gross and microscopic pathology. Under the conditions of this study, the MGX11-10 diets did not cause any treatment-related effects in rats following at least 90 days of dietary administration as compared with rats fed diets with the corresponding non-transgenic control diet and the basal-diet group. The MGX11-10 diets are considered equivalent to the diets prepared from conventional comparators. The results demonstrated that MGX11-10 wheat is as safe and wholesome as the corresponding non-transgenic control wheat. Highlights: Evaluate the subchronic oral toxicity of genetically modified MGX11-10 wheat. MGX11-10 wheat diets did not produce any adverse effects in rats during the study. MGX11-10 wheat are considered as safe and nutritious as the non-transgenic wheat.